2010
DOI: 10.1371/journal.pone.0011917
|View full text |Cite
|
Sign up to set email alerts
|

Retinoic Acids Potentiate BMP9-Induced Osteogenic Differentiation of Mesenchymal Progenitor Cells

Abstract: BackgroundAs one of the least studied bone morphogenetic proteins (BMPs), BMP9 is one of the most osteogenic BMPs. Retinoic acid (RA) signaling is known to play an important role in development, differentiation and bone metabolism. In this study, we investigate the effect of RA signaling on BMP9-induced osteogenic differentiation of mesenchymal progenitor cells (MPCs).Methodology/Principal FindingsBoth primary MPCs and MPC line are used for BMP9 and RA stimulation. Recombinant adenoviruses are used to deliver … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
151
0

Year Published

2010
2010
2013
2013

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 119 publications
(153 citation statements)
references
References 80 publications
2
151
0
Order By: Relevance
“…Using our previously established stem implantation assay Huang et al, 2012a;Huang et al, 2012b;Luo et al, 2010;Zhang et al, 2010), we injected the iMEFs transduced with BMP9 and HIF1a, simHIF1a, or RFP subcutaneously into the flanks of athymic nude mice for 4 weeks. The iMEFs transduced with RFP, HIF1a or simHIF1a alone failed to form any detectable masses (data not shown).…”
Section: Hif1a Is Crucial To Bmp9-induced Terminal Differentiation Ofmentioning
confidence: 99%
See 2 more Smart Citations
“…Using our previously established stem implantation assay Huang et al, 2012a;Huang et al, 2012b;Luo et al, 2010;Zhang et al, 2010), we injected the iMEFs transduced with BMP9 and HIF1a, simHIF1a, or RFP subcutaneously into the flanks of athymic nude mice for 4 weeks. The iMEFs transduced with RFP, HIF1a or simHIF1a alone failed to form any detectable masses (data not shown).…”
Section: Hif1a Is Crucial To Bmp9-induced Terminal Differentiation Ofmentioning
confidence: 99%
“…The first strand cDNA products were further diluted five-to tenfold and used as PCR templates. Semiquantitative RT-PCR (sqPCR) was carried out as described Rastegar et al, 2010;Su et al, 2011;Zhang et al, 2010;Zhu et al, 2009). PCR primers (supplementary material Table S1) were designed by using the Primer3 program to amplify the genes of interest (,150-180 bp).…”
Section: Rna Isolation and Semi-quantitative Rt-pcrmentioning
confidence: 99%
See 1 more Smart Citation
“…(4) Importantly, the presence of other soluble growth factors produced locally may potentiate the signaling of BMPs, such as insulin-like growth factor 2 (IGF-2) or retinoic acid, which were shown recently to potentiate the osteogenic effect of BMP-9. (54,55) …”
Section: Discussionmentioning
confidence: 99%
“…1a). Furthermore, this age-related diminution also occurred for the gene expression of OC, a late osteoblast differentiation marker (Pockwinse et al 1992;Zhang et al 2010). It has been demonstrated that PTHrP production-an important modulator of bone formation and remodeling in adult bone (Bisello (Martinez et al 2002).…”
Section: Resultsmentioning
confidence: 95%